The Relationship between Bank Deposits and Macroeconomic Variables in Ghana: A Co-Integration Approach - Opoku-Asante, Kofi; Owusu Kwaning , Collins; Arhenful, Peter; Ntiamoah, Jones; Asigbe-Tsriku, Gretel (Journal of Economics and Behavioral Studies, 2023)
This study examined the linkages between macroeconomic variables and how those relationships affect the total deposits of Ghanaian banks. The macroeconomic variables included in this study were Inflation (I), Monetary Policy Rate (MPR), Gross International Reserve (GIR), Public Debt (PD), Gross Domestic Product (GDP), GSE All share Index (GASI), Rate of change in Total Money Supply (M2+), deposits in the banking sector (TD). The study employed monthly data over the period (2015–2020); obtained from the Bank of Ghana monthly time series database. The data were analyzed using Gretl. The cointegration technique was employed in this study to gauge the long-term and short-term responsiveness of the connections. The ADF results indicated that the study variables were non-stationary. The econometric analysis suggested that the study variables, inflation (I), Gross Domestic Product (GDP), Public Debt level (PD), and Total Deposits (TD) in banks operating in Ghana, exhibited a significant positive long-run cointegration relationship. This suggested that the identified variables play a crucial role in explaining the fluctuations in total deposit levels within the Ghanaian banking industry. Bank deposit is strongly exogenous and moves to restore equilibrium through several short-run partial adjustments in the short-run. Also, in the short-run, only the GSE All-share index (GASI) significantly influenced bank deposits, but not in the long-run. In the long run, the relationship was still positive but insignificant.